A First Look at Spirituality in Daniel Serrão. Introductory Notes (Revista Iberoamericana de Bioética, 2019)
Although the concept of spirituality is briefly analyzed, the principal aim of this article is to study spirituality in the bioethical thought of Daniel Serrão. For this purpose, a hermeneutical analysis was carried out on a collection of published and unpublished articles by Daniel Serrão on spirituality and religion. Results: The analysis and interpretation of the texts revealed three important notes or characteristics in the conception of spirituality in Daniel Serrão: mystical, horizontal and transcendence. These notes or characteristics are fundamental for understanding, and coincide with the structure of their triadic thinking: metaphysical, scientific and cultural. When we enter the "heart of the Serronian discourse" we perceive that it presents a uniqueness in diversity. That is to say, there is no split between ethical, transcendental and scientific discourse. In bioethical thinking, spirituality is based on existential metaphysics, on essential metaphysics and on metaphysics in relation.
Keywords: spirituality; religion; bioethics